Comparison of Nephrolithiasis Prevalence in Two Bottlenose Dolphin (Tursiops truncatus) Populations - Smith, Cynthia R.; Venn-Watson, Stephanie; Wells, Randall S.; Johnson, Shawn P.; Maffeo, Natalie; Balmer, Brian C.; Jensen, Eric D.; Townsend, Forrest; Sakhaee, Khashayar (Frontiers in Endocrinology, 2013)
In humans, ammonium urate nephrolithiasis is rare in the Western hemisphere and more common in Japan and developing countries. Among a variety of risk factors, insulin resistance has been associated with urate nephrolithiasis in people. Bottlenose dolphins (Tursiops truncatus) are susceptible to ammonium urate nephrolithiasis, and it is believed that some populations are more likely to develop nephrolithiasis compared to others. In an effort to better understand population-based risk factors for ammonium urate nephrolithiasis in dolphins and their comparative value to humans, sonographic evaluation was performed on dolphins from a managed collection in San Diego Bay, California (n=40) and dolphins from a free-ranging, nearshore population in Sarasota Bay, Florida (n=39) to look for evidence of nephrolithiasis. While 14 (35%) of San Diego Bay dolphins evaluated for the study had sonographic evidence of nephrolithiasis, none of the Sarasota Bay dolphins had evidence of disease. Presence or absence of stones was confirmed by computed tomography in a subset of the San Diego collection (n=10; 4 dolphins with stones, 6 without stones). Age was identified as a risk factor, as dolphins with stones in the San Diego collection were significantly older than dolphins without stones (25.4 vs. 19.1 yrs, respectively; p=0.04). Additionally, San Diego dolphins included in the study were significantly older than Sarasota Bay dolphins (21.3 vs. 13.8 yrs, respectively; p=0.008). In addition to the previously reported risk factors of hypocitraturia and hyperinsulinemia in bottlenose dolphins, other potential factors include geographic location, managed versus free-ranging status, prey species, and feeding schedules.